Trait Rumination, Depression, and Executive Functions in Early Adolescence - Wagner, Clara A. (J Youth Adolesc, 2014)
Although deficits in executive functions have been linked with both depression and rumination in adulthood, the nature of the relationship between these constructs is not well understood and remains understudied in adolescence. The present study examined the relationship of rumination and depression to deficits in executive functions in early adolescence, a critical developmental period for the emergence of depression and rumination and the development of executive functions. Participants were 486 early adolescents (52.7% female; 47.1% African American, 48.8% Caucasian; 4.2% Biracial/Multiracial/Other; M age = 12.88 years; SD = .62) and their mothers, recruited through local schools. Measures included (a) a semi-structured diagnostic interview of the mother and adolescent, (b) youth self-report forms assessing depressive symptoms and trait rumination, (c) mother-report forms assessing demographic information, and (d) behavioral tests of executive function (sustained, selective and divided attention, attentional set shifting, and working memory). Gender moderated rumination-set shifting associations, such that rumination predicted better set shifting in boys only. The current level of depressive symptoms moderated rumination-sustained attention associations, such that rumination predicted better sustained attention in those with low levels of depressive symptoms and worse sustained attention in those with high levels of depressive symptoms. Rumination did not predict performance on other measures of executive functions. Likewise, depressive symptoms and diagnosis were not associated with executive functions. Implications for future research are discussed.